THE PROBLEM WITH STATE FINANCE PLANNING AND BUDGETING IN HIGHER EDUCATION - Ahmad Fakhrurraji; Prasetyono Prasetyono; Siti Musyarofah (Asia Pacific Fraud Journal, 2019)
This study aims to examine the management of state finances at the planning and budgeting stages. The mandate of the amendment of the 1945 Constitution which allocates a budget for education of 20% of the State Budget (APBN) is a challenge and constraint in managing the budget at an educational institution, especially higher education. The purpose of this study is to determine the problematic planning and budgeting of state finances. The object of this study is the leadership and the budget. This research is conducted in the institution “Ronggosukowati”, one of the government institutions in the sector of higher education in Indonesia. This research is a qualitative research with case study approach. The research is conducted using observation method by interviewing the informants. The results show that there is a problem that occurs at the planning and budgeting process in the institution “Ronggosukowati”. The solution strategy step is to address the problem.